Ceramic mold release agent and application thereof
By using ceramic mold release agent in titanium slag electric furnace cast iron, combined with high-temperature sintering technology of glaze and silicon oxide, a high-temperature resistant and dense glass thin layer is formed, which solves the problem of mold release in high-temperature and high-viscosity molten iron environment, and achieves high-quality mold release and mold protection of castings.
Patent Information
- Application Number
- CN202411893709.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
AI Technical Summary
In titanium slag electric furnace cast iron, the water-mold temperature is higher (usually above 1500℃) and has a high viscosity, which makes it difficult for traditional mold release agents to be released smoothly, which may lead to defects in the casting surface and damage to the mold.
A ceramic mold release agent is used, and its raw materials include 45 to 55 wt% glaze, 25 to 35 wt% silicon oxide, 8 to 12 wt% fluorane surfactant and 7 to 12 wt% composite chemical additives. Through high-temperature sintering, a dense and uniform glass thin layer can withstand high-temperature and high viscosity molten iron environment, ensuring the smooth mold release of the castings.
This release agent can effectively reduce the adhesion between the mold and cast iron, ensure smooth and defect-free surface of the casting, improve production efficiency and product quality, and extend the mold life.
Smart Images

Figure CN119681197A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of release agents for cast iron, and in particular relates to the technical field of ceramic release agents for cast iron. Background Art
[0002] The production process of cast iron usually includes steps such as mold preparation, molten iron smelting, casting, cooling and solidification. During the casting process, due to the large contact area and high temperature between the cast iron and the mold, adhesion is easy to occur, making the casting difficult to demold and may even damage the mold. Therefore, a release agent is usually required to avoid this situation.
[0003] Common casting release agents consist of lubricants, anti-sticking agents, and solvents. The lubricant forms a lubricating film on the mold surface, reducing friction with the cast iron. The anti-sticking agent reduces adhesion between the cast iron and the mold, facilitating demolding. The solvent adjusts the release agent's viscosity and fluidity, facilitating its application to the mold surface. The choice of release agent is typically determined by factors such as the cast iron type, shape, surface requirements, and production process. Generally speaking, for ordinary cast iron, a release agent with general properties is suitable, while for cast iron parts requiring high surface finish and precision, a release agent with specialized properties is preferred.
[0004] Currently, with the continuous development of industrial technology, the types and performance of release agents are constantly being innovated and improved. Traditional release agents are mainly based on ingredients such as paraffin and mineral oil, while modern release agents increasingly utilize environmentally friendly, high-performance silicones, polymers, and other new materials, offering better release effects, higher temperature tolerance, and lower environmental pollution. As an integral part of the cast iron production process, release agents play a vital role in improving production efficiency, reducing production costs, and improving the surface quality of castings. With the continuous advancement of industrial technology, the research and development and application of release agents will continue to improve, providing better support and guarantee for the development of the cast iron industry. This is especially true in titanium slag electric furnace cast iron, where the tapping temperature is relatively high, typically required to be above 1500°C. Therefore, the high-temperature resistance of the release agent becomes even more important.
[0005] Chinese patent application number CN201910358042.5 discloses a cast iron release agent and its production process. The composition and mass percentage of the release agent are: 0.5% to 1% graphite, 0% to 0.5% coke powder, 5% to 10% Guangxi white mud, 2% to 5% sericite, 1% to 2% coal slime and 82% to 90% water. The prepared release agent has the advantages of strong adhesion, fast sintering speed, ceramicization after sintering, and the ability to be sprayed during the cast iron process with good spraying effect; the production process includes the steps of batching, pulping and spraying. The release agent has high manufacturing efficiency and can adjust the ratio of some components according to actual needs. It has strong flexibility and can quickly solidify and sinter after being sprayed onto the cast iron mold. The release agent prepared in this application can quickly sinter to form a coating on the surface of the cast iron mold with only residual heat, and the coating is ceramicized and covered on the surface of the cast iron mold, realizing rapid coating of the release agent. However, the release agent formula of the application contains a lot of water. When the molten iron temperature is high (1500° C.), the release agent may crack after high-temperature dehydration, and it may not be able to withstand the test and is difficult to demould.
[0006] Chinese patent application number CN202210041781.3 discloses a release agent for hot casting molds, as well as its preparation and coating methods. This solves the problems of existing hot casting mold release agents, such as complex ingredients, narrow application range, poor erosion resistance, and inability to block high-temperature transmission for a short period of time. In addition, existing release agent coating methods have the phenomenon of alternating thin and thick strips of coating. The release agent of this invention includes 24 parts of pure water, 4 parts of silicon micropowder, 8 parts of high-temperature resistant auxiliary materials, and 1 part of sodium silicate. This invention uses silicon micropowder and high-temperature resistant auxiliary materials to emulsify to form a suspension liquid that is conducive to homogenization, and adds sodium silicate to form a water glass gel-like liquid. When this liquid is sprayed on the mold surface at 150-300°C, the components of the release agent coating lose some of their crystallization water and form a silicon dioxide network skeleton after hardening. This skeleton has a very small decrease in strength at high temperatures, and plays a role in resisting the erosion of the ferroalloy melt during ferroalloy casting. However, when the temperature of the molten iron exceeds 1500°C, the silica skeleton formed after the release agent hardens may collapse during the high-temperature casting process because it is not protected by a high-temperature resistant layer, resulting in poor casting quality and even damage to the mold.
[0007] In summary, the above patents all mention the preparation of release agents for cast iron, and improve the solidification speed and high temperature resistance of the release agents according to different cast iron scenarios. However, none of them point out how to solve the problem that the molten iron temperature is high and the viscosity is large in titanium slag electric furnace cast iron, and traditional release agents will not tolerate damage and thus cause surface defects of the castings after casting. Therefore, how to make the release agent for cast iron effectively cope with the complex molten iron environment with high temperature and high viscosity, and how to make the castings can be smoothly demolded, has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the Invention
[0008] In titanium slag electric furnace cast iron production, the molten iron has high temperatures, typically exceeding 1500°C, and high viscosity, typically exceeding 150 cP, making it difficult to successfully demold using traditional release agents. The first objective of the present invention is to provide a ceramic release agent for cast iron with a unique formulation and properties that can effectively cope with high-temperature, high-viscosity molten iron environments, reduce adhesion between the mold and cast iron, and facilitate smooth demolding of castings, thereby improving production efficiency and product quality.
[0009] The technical solution adopted by the present invention to solve its technical problem is:
[0010] A ceramic release agent comprises raw materials including: 45-55 wt% of glaze, 25-35 wt% of silicon oxide, 8-12 wt% of fluorocarbon surfactant, and 7-12 wt% of composite chemical additives.
[0011] The present application is based on the principle of ceramic firing, and the weight percentage of the glaze in the raw materials of the ceramic release agent of the present application is controlled to be 45-55wt%, and the silicon oxide is 25-35wt%. When the silicon oxide is fired at high temperature to form a skeleton, the glaze with this weight percentage is combined, wherein the organic matter is burned away, the crystal water is separated, the carbonate decomposes and emits carbon dioxide, and the high-temperature resistant component forms a hard glassy thin layer after melting at high temperature and cooling. After the release agent is formed and applied to the mold surface, it can have good mechanical strength and thermal stability. Usually, a small amount of micropores will appear on the surface of the high-temperature ceramic formed after the silicon oxide is sintered, and irregular burrs will form on the surface of the casting after the molten iron is poured into the mold for demolding. At higher temperatures (for example, molten iron 1500℃), the strength of the silicon oxide skeleton will also be destroyed, resulting in defects on the casting surface and damage to the mold. Balance the amount of glaze and silicon oxide. If there is too much silicon oxide and too little glaze, the film layer formed after sintering will be brittle and fall off, and defects will appear on the surface of the casting after demolding. If there is too much glaze and too little silicon oxide, it will lead to uneven sintering, which will also affect the quality of the casting when the molten iron viscosity is large. Unlike the traditional ceramic glaze firing, which is glazed on the surface of the formed ceramic body, the silicon oxide and glaze of this application are both given equal weight. After blending, they are supplemented with other additives. The glassy thin layer formed by the reaction of glaze and silicon oxide at high temperature can be dense and uniform, and the sintering molding speed is fast. Part of the glaze layer will also be coated on the surface of the casting. It is also easy to fall off after cooling for high-temperature molten iron with high viscosity, and it is not easy to form burrs, thereby ensuring the quality of the casting. On the contrary, it is understandable that the release agents in the prior art are often unable to withstand high temperature and high viscosity molten iron. After contact with molten iron, their own structure is destroyed and they cannot form a dense and uniform protective layer to separate the molten iron from the mold. Therefore, defects such as burrs will appear on the surface of the casting during demolding.
[0012] Specifically, the glaze selected in this application is for use in the ceramic industry. It is a mixture of epoxy resin, titanium dioxide, acetone, silicon oxide and rheological agent as main components. The rheological agent is preferably a polyurethane thickening rheological agent. Among them, epoxy resin has excellent adhesion. After being added, it can provide good coating and bonding properties for the glaze. It also has good heat resistance. After curing, it can improve the mechanical strength of the glaze to a certain extent and resist molten iron scouring. Titanium dioxide is also chemically stable. Generally, it does not react with most substances and can withstand higher temperatures. Acetone, as an organic solvent, provides a better mixing and flow environment for the glaze, is easy to coat, and is volatile at high temperatures, which is conducive to the formation of a thin layer of glass. The glaze also contains silicon oxide components, which are different from the oxide used to form the "embryo". Silicon is different. 25-35wt% of silicon oxide in the release agent mainly forms a skeleton that plays an overall supporting role, while the silicon oxide in the release agent mainly participates in the high-temperature reaction to generate glass, which can better block the contact between molten iron and the mold and protect the mold; the rheological agent can improve the rheological properties of the glaze, so that it can be evenly adhered during coating and form a smooth and continuous glaze surface after firing. The preferred polyurethane thickening rheological agent can further improve the stability of the glaze system and provide a better thickening effect, reduce the sagging phenomenon of the release agent during the coating process, and improve the coating quality. The glaze with the above components is preferably able to further cooperate with silicon oxide to form a high-temperature resistant, dense, and uniform glassy thin layer while ensuring a good coating effect of the release agent, so that the high-temperature and high-viscosity molten iron is easy to demould, and the surface of the casting formed after the molten iron contacts the release agent will also form a film. After demoulding, the casting is of high quality and has no burrs on the surface.
[0013] Furthermore, 7 to 12 wt% of a composite chemical additive is added to the raw material, and its specific composition is: 70 wt% silicone oil, 15 wt% antioxidant and 15 wt% ammonium chloride. The addition of the above composite chemical additive can improve the antioxidant, anti-corrosion and anti-friction properties of the release agent, and at the same time enhance the adhesion ability and water resistance of the release agent, so that it can better coat and protect the mold, sinter evenly, and extend the life of the mold.
[0014] Furthermore, 8-12 wt% of a fluoroalkane surfactant is added to the raw materials, specifically comprising 70 wt% of a fluoroalkane siloxane and 30 wt% of acetone. Fluoroalkane surfactants have high surface activity and can significantly reduce the surface tension of the release agent, facilitating its even spreading. The addition of 30 wt% of acetone improves mixing of the silicon oxide with the glaze. A certain amount of fluoroalkane surfactant also helps maintain the stability of the release agent at high temperatures.
[0015] Preferably, through the exploration of this application, it is found that when the raw material ratio of the release agent is: 50wt% glaze, 30wt% silicon oxide, 10wt% fluorocarbon surfactant, and 10wt% composite chemical additives, the ceramic release agent can withstand a high temperature of 1550°C and a viscosity of molten iron between approximately 150cP and 530cP, and is suitable for more high-temperature cast iron scenarios.
[0016] Specifically, the glaze has a fineness of 500 mesh, and the silicon oxide is industrial-grade silicon oxide powder with a fineness of 600 mesh. Controlling the fineness of the glaze and silicon oxide ensures a more uniform coating after mixing, facilitates high-temperature sintering, and better bonds to form a smoother, denser thin layer surface, facilitating demolding of castings.
[0017] During use, the ceramic release agent containing the above-mentioned raw materials is poured into a blender, and water is added and stirred until evenly mixed. The release agent can be used to release cast iron from the mold. The ceramic release agent disclosed in this application can be used in titanium slag electric furnace cast iron where the molten iron temperature and viscosity are both high. It is simple to use: simply add an appropriate amount of water, stir evenly, and apply to the mold surface for release. The high temperature of the molten iron, approximately 1500°C, forms a dense, smooth, glassy film. This film is easily removed from the molten iron after cooling, and effectively protects the mold.
[0018] Specifically, the water added to the mixer is industrial-grade deionized water, with the amount added being approximately 60-70% by weight of the ceramic release agent. Industrial-grade deionized water has a higher purity and fewer impurities, further ensuring that the release agent forms a uniform and strong thin layer. Furthermore, when the water content is less than 60% by weight, the mixture is thick, resulting in incomplete mixing and uneven coating. When the water content is greater than 70% by weight, the mixture is thinner, resulting in less adherence to the wall during coating and poor coating results.
[0019] Compared with the prior art, the embodiments of the present invention have at least the following beneficial effects:
[0020] 1. The present invention uses glaze and silicon oxide as the main components of the release agent, balances the dosage of the two, controls the main component glaze in the release agent raw materials to be 45-55wt%, and silicon oxide to be 25-35wt%, and combines with other chemical additives. After coating, the high temperature of the molten iron causes the raw materials to react rapidly to form a dense, uniform, and mechanically strong protective layer. The protective layer can withstand high molten iron temperatures (above 1500°C) and has a good demoulding effect on high-viscosity molten iron, thereby ensuring the quality of the casting and preventing defects such as burrs.
[0021] 2. The release agent prepared by using the raw materials of the present invention has strong uniformity, good fluidity, appropriate viscosity, and rapid film formation, and can be well used for high-temperature cast iron demoulding. It is preferably added with 60 to 70 wt% of water to disperse the release agent evenly, so that the coating effect is better and the performance of the protective layer formed is also better.
[0022] 3. The release agent prepared by the method of the present invention has good high temperature resistance and demoulding effect, the raw material composition is simple and the consumption per ton of iron is only 2 to 3 kilograms. It can be reused after recovery, which effectively improves the stability and use efficiency of the ceramic release agent for cast iron. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following is a brief introduction to the drawings required for use in the embodiments and comparative examples. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.
[0024] Figure 1 This is a flow chart for preparing the ceramic release agent in Example 2 of the present invention. DETAILED DESCRIPTION
[0025] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, all are conventional products that can be purchased commercially.
[0026] S1: preparing a release agent: taking 45-55 wt% of glaze, 25-35 wt% of silicon oxide, 8-12 wt% of fluorocarbon surfactant and 7-12 wt% of composite chemical additives to prepare a ceramic release agent, pouring the release agent into a blender, adding 60-70 wt% of water in an amount equal to the weight of the release agent and stirring evenly.
[0027] S2: Clean the mold: Before applying the release agent, make sure the mold surface is clean and dust-free. Use a clean cloth or cotton ball dipped in an appropriate amount of anhydrous ethanol to thoroughly wipe the mold surface.
[0028] S3: Apply release agent: After cleaning the mold surface, shake the container of ceramic release agent to ensure uniformity and improve the application effect. Use a small brush to evenly apply the release agent to the mold surface, ensuring that every part is covered and the application layer is as even as possible.
[0029] S4: Drying: After applying the release agent, wait 5 minutes for the release agent to dry on the mold surface. The drying time varies depending on the properties of the release agent and environmental conditions, and generally takes several minutes to several hours. During the waiting period, you can use a fan or other ventilation equipment to accelerate the drying process.
[0030] S5: Secondary coating: After the release agent has dried on the mold surface, apply the release agent evenly to the mold surface again. Repeat the above coating operation twice to ensure that each mold surface is evenly coated with the release agent.
[0031] S6: Pouring the Molten Iron: After completing the above steps, the molten iron can be poured into the mold. When pouring the molten iron, be careful not to pour it in too quickly to avoid splashing or damaging the mold. After the molten iron is poured in, wait for it to cool and solidify before removing it from the mold to obtain the casting.
[0032] It should be noted that, unless there is a conflict, the embodiments and features of the embodiments of the present invention may be combined with each other. The present invention will be described in detail below with reference to specific embodiments. The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0033] Example
[0034] The embodiments of the present invention are implemented according to the technical solutions in the above embodiments, and the specific implementation is shown in Table 1 and Figure 1 As shown, Figure 1 This is a flow chart for preparing the ceramic release agent in Example 2 of the present invention. Examples 1 to 3 all use titanium slag electric furnace cast iron. After the molten iron is cooled, the mold is demolded, and a uniform film is formed on the surface of the casting. After the film is torn off, the surface of the casting is smooth and flawless, without any defects such as bubbles and burrs. In addition, due to the good peelability of the release agent, the residual amount of the release agent on the surface of the casting is less than 0.01g / cm 2 .
[0035] Table 1 Specific implementation of the embodiment
[0036] Example glaze Silicon oxide Fluorocarbon surfactants Composite chemical additives Molten iron temperature Molten iron viscosity Example 1 45wt% 35wt% 8wt% 12wt% 1518℃ 437cP Example 2 50wt% 30wt% 10wt% 10wt% 1550℃ 406cP Example 3 55wt% 25wt% 12wt% 7wt% 1523℃ 425cP
[0037] Comparative Example 1
[0038] The implementation method of Comparative Example 1 is implemented with reference to the Chinese patent application number CN202210041781.3, wherein the raw materials include 24 parts of pure water, 4 parts of silicon micropowder, 8 parts of high temperature resistant auxiliary materials, and 1 part of sodium silicate, in parts by weight.
[0039] The cast iron this time is titanium slag electric furnace cast iron. The molten iron temperature is about 400℃ and the viscosity is about 413cP. After the molten iron is cooled and demolded, there are slight defects on the surface of the casting.
[0040] Comparative Example 2
[0041] The implementation of Comparative Example 2 is basically the same as that of the embodiment, except that the amount of the release agent raw materials is changed. The raw materials include: 40wt% glaze, 40wt% silicon oxide, 7wt% fluorocarbon surfactant, and 13wt% composite chemical additives.
[0042] The cast iron was titanium slag electric furnace cast iron. The molten iron temperature was about 1517℃ and the viscosity was about 438cP. After the molten iron cooled, it was demoulded. There were many defects on the casting surface, and the residual amount of release agent was 0.06g / cm 2 .
[0043] In summary, it can be seen that the ceramic release agent for cast iron of the present invention has the best effect under the above process operation with the corresponding implementation effect of Example 2, which can withstand a high temperature of 1550°C. After the molten iron is cooled, the mold is demoulded and the film on the surface of the casting is torn off. The casting is smooth and flawless, without defects such as bubbles and burrs, and the residual amount of the release agent is less than 0.01g / cm 2 , which shows that the release agent prepared by the method of the present invention can withstand high-temperature, high-viscosity molten iron, and forms a dense and uniform protective layer, so that the obtained castings are of high quality and free of defects.
[0044] The embodiments described above are some embodiments of the present invention, rather than all embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed application, but merely represents selected embodiments of the present invention. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making creative efforts are within the scope of protection of the present invention.
Claims
1. A ceramic release agent, characterized in that: Ingredients include: The glaze material is 45-55wt%, the silicon oxide is 25-35wt%, the fluorocarbon surfactant is 8-12wt%, and the composite chemical additive is 7-12wt%.
2. A ceramic release agent according to claim 1, characterized in that: Ingredients include: The glaze comprises 50 wt %, silicon oxide 30 wt %, fluorocarbon surfactant 10 wt %, and composite chemical additive 10 wt %.
3. A ceramic release agent according to claim 1 or 2, characterized in that: The fineness of the glaze is 500 mesh, and the fineness of the silicon oxide is 600 mesh.
4. A ceramic release agent according to claim 1 or 2, characterized in that: The glaze is a mixture of epoxy resin, titanium dioxide, acetone, silicon oxide and rheological agent.
5. A ceramic release agent according to claim 1 or 2, characterized in that: The fluorocarbon surfactant is composed of 70 wt % of fluorocarbon siloxane and 30 wt % of acetone.
6. A ceramic release agent according to claim 1 or 2, characterized in that: The composite chemical additive is: 70wt% silicone oil, 15wt% antioxidant and 15wt% ammonium chloride.
7. An application of a ceramic release agent as claimed in claim 1 or 2, characterized in that: The method includes pouring a ceramic release agent into a mixer, adding water and stirring evenly, and then the mixture can be used for cast iron demoulding.
8. The use of a ceramic release agent for cast iron according to claim 7, characterized in that: The water added is industrial-grade deionized water, and the amount of water added accounts for 60-70 wt % of the ceramic release agent in the mixer.
Citation Information
Patent Citations
Iron casting release agent and production process thereof
CN110090918A
Release agent for hot casting mold as well as preparation method and coating method of release agent
CN116475357A
Improvement for backlight module support
CN1523425A